Multiplicidade de soluções para sistemas do tipo Schrödinger-Poisson - Oliveira, Alcionio Saldanha de (2014)
In this work, we will use the Mountain Pass Theorem, Ekeland s Variational Principle, the Concentration-Compactness Principle, the Brezis & Nirenberg Method, Penalization Method and some properties involving Nehari manifolds to obtain existence and multiplicity of solutions for the following class of elliptic systems. () 8<: u + V (x)u + u = r(x; u) em R3; = u2 em R3; where r : R3 R ! R is a function that has critical growth.